The nature of natural philosophy in the late Middle Ages - Grant, Edward (Studies in philosophy and the history of philosophy, 2010)
When did modern science begin? -- Science and the medieval university -- The condemnation of 1277, God's absolute power, and physical thought in the late Middle Ages -- God, science, and natural philosophy in the late Middle Ages -- Medieval departures from Aristotelian natural philosophy -- God and the medieval cosmos -- Scientific imagination in the Middle Ages -- Medieval natural philosophy : empiricism without observation -- Science and theology in the Middle Ages -- The fate of ancient Greek natural philosophy in the Middle Ages : Islam and western Christianity -- What was natural philosophy in the Middle Ages? -- Aristotelianism and the longevity of the medieval worldview